The Lancaster County Juvenile Reentry Project - Fousek, Sommer (2014)
In order to establish a best practice model for juveniles reentering the community, Lancaster County brought multiple agencies together in 2012 and began to develop a systematic juvenile reentry approach, which became known as the “Reentry Project.” By January 2013, Lancaster County had contracted with multiple agencies to ensure this new approach was used when youth were returning to the community